MEMPREDIKSI LOYALITAS DAN KOMUNIKASI DARI MULUT KE MULUT: STUDI EMPIRIS PADA SUATU PUSAT KEBUGARAN - Melva Lasmaria Manalu; Sabrina Oktoria Sihombing (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
This research examines a cognitive-affective-conative baseline model which proposed by Chiouet al. (2002). According to the model, perceived service quality (both tangible company-relatedand employee-related factors) is modeled antecedent to satisfaction and trust, which in turn areantecedents to customer loyalty responses (word of mouth and traditional loyalty). The sampleof this research was 233 students. Respondents were collected by using purposive samplingtechnique. Structural equation modeling (SEM) was used to analyze the data. The results showthat all research hypoteses were supported. This paper also provides the implications for theoreticaland managerial and offers directions for future research.Key words: service quality, loyalty, word-of-mouth